Whatever happened to history of science? How scholarship became politicized story-telling - John Eric Rayner Staddon (Duke University, Center for the History of Political Economy (CHOPE), 2020)
In this piece I look at just one small corner of science history touching on biology, psychology and political science. I tend to agree with Paul Feyerabend's Against Method to the extent that if there is no algorithmic scientific method, then science is best understood through examples. The same is surely true of history of science: there is no template. In this article I discuss five books to illustrate three trends: a retreat from political neutrality; downplaying the truth (however assessed) of scientific claims as a reason for their acceptance; and the desire for a good story, preferably a capitalist plot.
Keywords: 330; Nancy MacLean; John Desmond Bernal; Naomi Oreskes; Erik Conway; Rebecca Lemov